INTERNATIONAL COMPETITION IN CENTRAL ASIA PERSPECTIVE IN INTERNATIONAL RELATIONS - Jabber , Mais Nouman; Abdul Salam Faraj Ali Farhat (International Journal Multidisciplinary (IJMI), 2025)
Objective: The problem of the research was that Central Asia has strategic elements that helped to create a hidden conflict between international powers for the sake of the limit of influence and domination. Method:  The research likely used qualitative political analysis through a geopolitical lens, examining post-9/11 developments, international agreements, and regional dynamics involving the United States, European Union, and Russia. Results: The geopolitical movement of the United States, the European Union and Russia intensified after the events of September 11, 2001 , and the competition between these forces increased to strengthen their political, economic and military influence, in light of the republics with fragile political, economic and military pillars that helped to attract international powers under the pretext of helping countries and overcoming the challenges they face. Therefore, multiple agreements were concluded that contributed to penetrating Central Asia, which raised the ire of Russia, which considered it a threat to Russian national security and fear of being surrounded and besieged by these countries and Western forces and their role in international relations. Novelty: Central Asia represents a strategic and geopolitical importance, due to its location and resources in the vital field of Eurasia , which is a buffer zone between Asian and regional powers, and the region represents a pivotal intersection point for international powers.